Lending relationships in loan renegotiation: Evidence from corporate loans - Katharina Plessen-Mátyás (European Central Bank (ECB), 2021)
This paper presents evidence that personal relationships between corporate borrowers and bank loan officers improve the outcomes of loan renegotiation. Analysing a bank reorganization in Greece in the mid-2010s, I find that firms that experience an exogenous interruption in their loan officer relationship confront three consequences: one, the firms are less likely to renegotiate their loans; two, conditional on renegotiation, the firms are given tougher loan terms; and three, the firms are more likely to alter their capital structure. These results point to the importance of lending relationships in mitigating the cost of distress for borrowers in loan renegotiations.
Keywords: G21; L14; E44; E58; O16; 330; loan renegotiation; bank branch closures; loan officers; corporate credit